2017
DOI: 10.3892/ol.2017.6972
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NF-κB and PTEN in osteosarcoma and its clinical significance

Abstract: We investigated the role of nuclear factor-κB (NF-κB) and phosphatase and tensin homolog deleted in chromosome 10 (PTEN) in the pathogenesis of osteosarcoma and its relationship with prognosis. Immunohistochemical method was used to detect the expression of NF-κB and PTEN in osteosarcoma and adjacent tissues. RT-PCR was used to detect the expression of NF-κB and PTEN mRNA in osteosarcoma and adjacent tissues. Western blotting was used to detect the expression of NF-κB and PTEN in osteosarcoma and adjacent tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…These studies suggest that FER1L4 functions as a ceRNA of miR-18a-5p in OS. Phosphatase and tensin homologue (PTEN), located on chromosome10q23, has been reported to be downregulated in OS tissues and cell lines, and low PTEN expression was associated with poor prognosis [28][29][30]. In addition, overexpression of PTEN significantly inhibits OS cell proliferation, migration, and invasion, and induces cell apoptosis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that FER1L4 functions as a ceRNA of miR-18a-5p in OS. Phosphatase and tensin homologue (PTEN), located on chromosome10q23, has been reported to be downregulated in OS tissues and cell lines, and low PTEN expression was associated with poor prognosis [28][29][30]. In addition, overexpression of PTEN significantly inhibits OS cell proliferation, migration, and invasion, and induces cell apoptosis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…PTEN is a tumour suppressor gene that controls cell and apoptosis in a variety of cancers [41]. It has been reported that PTEN expression was declined in diverse malignant cancers such as breast cancer and prostate cancer [42]. More importantly, PTEN negatively regulates PI3K/AKT pathway [43].…”
Section: Discussionmentioning
confidence: 99%
“…Upon further review, 14 were excluded because they were not clinical studies. Finally, 13 articles [16–18,25–34] published from 2005 to 2017 were adopted in this meta–analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%